An evaluation of the conditions of service and human resources policies as anti-dotes of corruption: case of Norton Town Council. - Shiripinda, Gladmore (Midlands State University, 2014)
The purpose of the research was to evaluate the effectiveness of the Human Resources (HR) policies and the conditions of service as anti-dotes of corruption. The study was influenced by the rampant rise of corruption practices in the local government sector. The research sought to identify: Causes of corruption at Norton Town Council (NTC), Human Resources policies and conditions of service in fighting corruption, the problems being faced in the implementation of HR policies and the conditions of service and lastly to evaluate the effectiveness of the HR policies and conditions of service in fighting corruption at NTC. Themes reviewed in the literature review were consequences of corruption, what corruption is, common forms of corruption, what Human Resources Management is, what HR policies are and why HR policies. Anti-corruption HR policies were also discussed and they included reward management, recruitment and selection, equal opportunity and career advancement and selection policy. Conditions of service were also reviewed. The research used both qualitative and quantitative researches and the research was also a descriptive one. The study population was 274 which was sample sized to 27 participants. Sampling techniques used were random sampling and purposive sampling. In random sampling names of participants were put in a box and shuffled fairly and names of participants were picked from the box. In purposive sampling participants were selected judgmentally basing on participants’ in-depth information and experiences in the area of study. Interviews and questionnaires were used as data collection instruments. Major research findings were that the causes of corruption at NTC are delayed salaries, low remuneration, politics, lack of clear cut HR policies, poor penalties on offenders and greediness. Council is using out-dated conditions of service which were drafted way back in 1994. The identified anti-corruption HR policies in place at NTC are Recruitment and selection, reward management and equal opportunity. Political interference, procrastination, insufficient funding and non-involvement of employees in the formulation process were concluded as the problems being face by the council in the implementation of HR policies and conditions of service. The recommendations were that the Council should implement and put to practice HR policies and conditions of service that are vital in promoting ethical standards and make sure that such policies are not only paper based but also that they are practiced, Council should pay employees’ salaries in time, Council should revisit its employment conditions of service for various adjustments and amendments, the local authority should create attractive remuneration packages for its employees. The Council should increase salaries for its employees who earn below the poverty basket of US$500. 00 so as to avoid supplementation of income through unethical means. Policy formulation process should also cater for the participation of employees. The council should effect stiff penalties on offenders like dismissal, arrests, demotion among others. Corrupt practices have been rampant because there is lack of adequate penalties on the fraudsters thus more employees have taken the toll in practicing unethical activities, council should promote political will and commitment (ethical leadership) from the councillors to lead by example. The Council should enshrine whistle blowing protection in its conditions of service or to formulate it as a policy thus providing a chance to people with information to unearth corrupt activities.